West Bengal : Health Policy Note - World Bank (Washington, DC, 2013)
This Policy Note sets out the options for future development of the health system together with the Department of Health and Family Welfare, based on an analysis of existing data on health outcomes, health financing utilization of current health infrastructure in the public and private sector, a description and assessment of the Government of West Bengal's current policy and developments, and of donors' recent investments and plans for the future. The purpose of this Note would be to set the basis for identifying key strategic directions for reform of the health sector. The report is structured as follows: After the executive summary, section 1 discusses the current health status. Section 2 examines health care financing. Section 3 describes health delivery systems. Section 4 measures health system performance. Section 5 reviews recent health reforms. Section 6 elaborates what needs to be strengthened and what needs to be done differently.